PENGARUH MEDIA SOSIAL, HARGA, DAN LOKASI TERHADAP KEPUTUSAN KUNJUNGAN KONSUMEN - Dadan Purnama; Titin Hargyatni (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
This scholarly inquiry endeavors to dissect the intricate dynamics through which social media—intertwined with pricing schemes and geographical accessibility—exerts influence in sculpting the cognitive and behavioral inclinations of consumers toward their decision to visit Resto Kedai Darma, situated in Klaten, Central Java. The declining number of consumer visits became the motivation for this research, which is presumed to be related to suboptimal digital promotion, perceptions of prices that do not match service quality, and the restaurant's location outside the city center. The core demographic profile identified in this study encompasses individuals aged 17 to 40 who exhibit consistent engagement with social media platforms. A total of 100 participants were selected utilizing an incidental sampling technique. Empirical data acquisition was facilitated through the dissemination of structured questionnaires, followed by analytical processing via multiple linear regression techniques, operationalized using SPSS software version 27. The empirical findings reveal that pricing exerts a statistically significant and positive influence on consumer visit decisions, while social media and location do not show significant effects. The coefficient of determination (Adjusted R²) is 11.6%, indicating that the triadic constructs of social media engagement, pricing dynamics, and spatial accessibility collectively exert measurable impacts, explaining 11.6% of the variation in consumer visit decisions. The findings suggest that price is a dominant factor influencing customer decisions, while social media and location require further strategic optimization to attract more visitors.